Random laser from engineered nanostructures obtained by surface tension driven lithography. Issue 3 (25th February 2013) - Ghofraniha, Neda; Viola, Ilenia; Maria, Francesca Di; Barbarella, Giovanna; Gigli, Giuseppe; Conti, Claudio
<x xml:space="preserve">Abstract</x> The random laser emission from the functionalized thienyl‐S, S‐dioxide quinquethiophene (T5OCx) in confined patterns with different shapes is demonstrated. Functional patterning of the light emitter organic material in well defined features is obtained by spontaneous molecular self‐assembly guided by surface tension driven (STD) lithography. Such controlled supramolecular nano‐aggregates act as scattering centers allowing the fabrication of one‐component organic lasers with no external resonator and with desired shape and efficiency. Atomic force microscopy shows that different geometric pattern with different supramolecular organization obtained by the lithographic process tailors the coherent emission properties by controlling the distribution and the size of the random scatterers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>